2017
DOI: 10.18203/issn.2454-5929.ijohns20171178
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of FNAC in diagnosing thyroid swelling: a retrospective study

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Aim of the study was to determine the accuracy of FNAC in diagnosing thyroid swellings. </span></p><p class="abstract"><strong>Methods:</strong> <span lang="EN-IN">A Retrospective study was conducted over a period of one year (September 2014 to September 2015), which included 54 patients, who presented with thyroid swelling to the ENT outpatient department.All the above patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“… 2 The great impact on advancement and improvement of healthcare due to the implementation of the thyroid FNAC has been illustrated in numerous studies that have compared the accuracy of FNAC with the final histopathology diagnosis. 3 - 5 Overall, research has found that FNAC has a high diagnostic sensitivity and specificity levels. Additionally, patients with preoperative FNAC had an optimal surgical treatment, compared with patients who had no preoperative FNAC.…”
mentioning
confidence: 99%
“… 2 The great impact on advancement and improvement of healthcare due to the implementation of the thyroid FNAC has been illustrated in numerous studies that have compared the accuracy of FNAC with the final histopathology diagnosis. 3 - 5 Overall, research has found that FNAC has a high diagnostic sensitivity and specificity levels. Additionally, patients with preoperative FNAC had an optimal surgical treatment, compared with patients who had no preoperative FNAC.…”
mentioning
confidence: 99%